On Distributed Parameter System Identification with a Priori Information as Constraints - Rafajłowicz, E. (Engineering Transactions, 1984)
The identification procedure presented in the paper makes it possible to determine the unloaded estimator of parameters of a system with distributed. parameters. They are derived by minimization of the quality functional in the quadratic form with the constrains being tak.en into account. Various properties of the procedure proposed are discussed, and a numerical example is presented.